ANALISIS KEMAMPUAN BERBICARA ANAK USIA 4-5 TAHUN (STUDY DESKRIPTIF) DI TAMAN KANAK-KANAK DAREL HIKMAH KOTA PEKANBARU - Yully Berti Berti; Wilson '; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is motivated because Based on preliminary observations in the field, there are still a phenomenon researchers found children aged 4-5 years do not dare to verbally convey good wishes. When the teacher asks the child seems to want to say something after a child is given the opportunity did not dare to deliver. This problem often faced by teachers in class, whereas when playing with friends is still limited to the word yes, willing and yet have long sentences, at the time the child is given questions only silent even though the teacher has to stimulate the child to speak fluently. Another emerging phenomenon is based on the observation in kindergarten Darel Vocabulary Lessons that children have less, visible from every story morning child does not want to tell in front of the class and the child chooses to be silent or to hear his story. In this analysis is an indicator of all children have a good capacity in accordance with the age, namely 4-5 years, where the child has been able to speak fluently by the time the teacher explains the classroom, it also shows that the category of each capability vary, but the average have demonstrated the ability of developing very well. Results of data collection about the ability of children aged 4-5 years speaks very well developed when all components of education both at school and at home can work together and give each other positive contributions. Keywords: speech, early childhood.